Heliostat tailored to Brazil - Pfahl, Andreas; Bezerra, Pedro Henrique Silva [UNESP]; Hölle, Erwin; Liedke, Phillip; Teramoto, Érico Tadao [UNESP]; Hertel, Johannes; Lampkowski, Marcelo [UNESP]; De Oliveira, Celso Eduardo Lins (International Solar Energy Society (ISES), 2015)
For Brazil, it is important to realize a high national production share because of high import fees and to obtain cost reduction related to implementation of the CSP technology. The rim drive concept offers an alternative for expensive heliostat drive solutions with slew and linear drives from abroad. Sandwich facets (which are usually foreseen for rim drive heliostats) are not available from Brazilian manufacturers and are replaced by a steel frame work structure with mounted 4 mm glass mirrors. The mirrors were bent along one axis. A two-axis curvature, while being optically more precise, would result in excessive stress of the mirrors when short focal lengths (present case: 30 m) have to be attained. For an 8 m2 heliostat, the mirror panel was divided into six stripes. The stripes have to be canted to reach a sufficiently small focal spot. A prototype heliostat was designed and built. High stiffness and sufficient durability of the mirror facets against wind loads was reached. For the considered heliostat area of 8 m2, the proposed framework design could be further simplified, but for 16m2 heliostats (or bigger) it seems to be adequate. A heliostat with high local production share can be accomplished using the rim drive concept. High stiffness can be reached also without sandwich facet mirrors by using a framework mirror support structure with one rim as part of it. Short focal lengths can be achieved by dividing the mirror into several stripes bent in one single axis. The components described increases the feasibility of be manufactured in Brazil and makes possible to avoid increments in CSP plant costs related to import fees.
Keywords: Fem; Heliostat; Local content; Mirror facet; Solar tower plant; Wind loads